Government Governance in the Management of Border Areas: Perspective of Good Governance - Verawati Skaut; M. Angela Merici Siba; Yosef Kristoforus Taekab (Jurnal Kebijakan Publik, 2026)
Border area management is a strategic issue in public governance because it is closely related to national sovereignty, equitable development, public service delivery, and community welfare. North Central Timor Regency (Timor Tengah Utara/TTU), as one of Indonesia’s border regions directly adjacent to the Democratic Republic of Timor-Leste, continues to face various governance challenges, including suboptimal intergovernmental coordination, limited institutional capacity, inadequate implementation of good governance principles, and the lack of integrated border management policies. This study aims to analyze governance in the management of the North Central Timor border area from a good governance perspective and to identify research findings, implications, and research gaps based on the existing literature. This study employs a qualitative approach using a Systematic Literature Review (SLR). The units of analysis consist of eight scholarly articles retrieved from Google Scholar, Scopus, SINTA, DOAJ, and Crossref databases, as well as relevant government policy documents related to border area management. Data were collected through document analysis using literature selection guidelines based on inclusion and exclusion criteria following the PRISMA 2020 framework. The data were analyzed using thematic synthesis through data reduction, coding, thematic categorization, cross-study comparison, and interpretation based on the perspectives of new governance, border governance, and good governance. The findings reveal that governance in the management of the North Central Timor border area is characterized by three major themes: institutional governance and intergovernmental coordination, the implementation of good governance principles at the local government level, and border area development strategies as instruments for strengthening national sovereignty.